Mental health in distance learning: a taxonomy of barriers and enablers to student mental wellbeing. (3rd April 2023) - Lister, Kate; Seale, Jane; Douce, Chris
ABSTRACT: Student mental health is a critical issue in higher education. It is understood that higher education can act to trigger or exacerbate mental health difficulties, but research in this area has focused primarily on campus environments, identifying stressors such as halls of residence. Since distance learning students disclose mental health issues at a higher rate than campus students, and completion and progression gaps are on a par with the sector, the barriers and enablers to mental wellbeing in distance learning must be understood. This paper reports on a qualitative study that investigated barriers and enablers to mental wellbeing and study success that students experienced in distance learning. Sixteen distance learning students and five tutors were interviewed using narrative enquiry; students told their own stories and tutors told stories of students they had supported. Barriers and enablers were identified across different aspects of study, skills-development and the distance learning environment, and are presented in a taxonomy of barriers and enablers that suggest a range of implications for distance learning educators and policy developers.